A qualitative conceptual framework to tackle skill shortages in offsite construction industry: aÂ scientometric approach - Saad, S. (Emerald Group Holdings Ltd., 2021)
Purpose: This study assessed the key construction technology trends and tracked the impact of these developments on labor influencing factors in an effort to alleviate the limitations posed by skilled labor scarcity in offsite construction (OSC). Design/methodology/approach: The study followed systematic literature review to acquisition initial data sets. The data retrieved form identified databases was then subjected to scientometric analysis. In next stage, disruptive factors were identified to produce a conceptual framework followed by its practical application for an OSC firm. Findings: This study identified seven construction technologies with a potential to disrupt OSC in future. The study also developed a conceptual framework as a benchmark to help establish further frameworks for policy interns in OSC. Research limitations/implications: The review conducted only takes into account the literature from 2009 to March 2021. Any prior to the date and unpublished studies were not included in study. Practical implications: A proper utilization of conceptual framework can contribute to technological adoption significantly lowering the need of labor in OSC industry. Moreover, the established discussion on understanding the purpose of deploying latest technology may reduce additional costs, management, time and allocation of labor resources. Social implications: This study provides a mechanism to intern OSC policymakers to impartially incorporate the latest technology in OSC. Originality/value: This study fulfilled an identified need to study latest technological trends in OSC by utilizing bibliometric tools with SLR. The disruptive categories and factors highlighted by the study were not identified in a systematic manner in previous studies, which could further enhance the implementation of latest construction technology in OSC. Â© 2021, Emerald Publishing Limited.